Processing and Utilization of Sago palm in Central Moluccas - Mahulette, Ferymon; Matulessy, Yoin M; Pattiasina, Eifan B; Rupilu, Marselina R (University of Merdeka Malang, 2021)
Indigenous people in Moluccas consumed sago flour as a main food. It is extracted from the pith of the sago palm (Metroxylon sp) by traditional and modern processing. Sago flour can be processed into various local food products which are local wisdom of the Moluccan. These products are produced by a very diverse community. In addition, stalks and leaves of sago tree can also be used for building construction. This study aims to describe the processing techniques and utilization of sago palm in Central Moluccas. This research was descriptive qualitative. Data was collected from direct observations and documentation from volunteers in several villages only in Central Moluccas, i.e. Hila village (Ambon), Tuhaha and Ouw villages (Saparua), Kamarian and Iha-Luhu villages (West Ceram), and several villages in Geser and Gorom islands (East Ceram). The results showed that sago processing in Central Moluccas was done manually (traditional) or machinery. The processing technique these plants was relatively the same but the processed sago products vary greatly in each village. Sago processed products such as papeda, sagu lempeng, sagu tumbuk, serut, sagu buksona, sagu lakar and sagu fitrah. Besides it flour used as food, stalks and leaves of sago tree are used to build traditional houses, baileo and worship houses. This research was expected to conserve of the pukul sagu tradition and sago processed products to support the tourism in Central MoluccasÂ DOI:Â https://doi.org/10.26905/lw.v13i1.4406